Pengaruh Media Pembelajaran Berbasis Augmented Reality Dan Gaya Belajar Terhadap Kkemampuan Berpikir Tingkat Tinggi Pembelajaran IPA Pada Siswa Kelas VII UPTD SMP Negeri 3 Bangkalan - Rusdiana, Efi; Tri Eka, Soesiana; Sunardjo, Sunardjo (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2024)
The observations conducted at SMPN 3 Bangkalan during the odd and even semesters of the 2022/2023 academic year revealed that the learning outcomes in science subjects were not optimal. The majority of students scored below the Minimum Completion Criteria of 80. The objective is to test, prove, and describe whether there is an interaction effect between the use of augmented reality-based learning media and learning styles on the ability to think at a high level in science among students in grade seven at UPTD SMP Negeri 3 Bangkalan. This research employs quantitative methodology, which entails the use of numerical data and statistical analysis. The design of this research is ex post facto, meaning that data were collected after all the events in question had occurred without any intervention. The results of the analysis indicate that the value of Fhitung = 3.220 with Significance (Sig.) 0.048. The proposed hypothesis is accepted or rejected based on the F value and significance (Sig.). The criteria are met if the F value is greater than the F table value and the significance is less than 0.05 (alpha). The null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. The significance value (asymp sig.) is 0.048, as shown in the output. Given that the significance value is less than 0.05, the null hypothesis is rejected. This indicates that there is an interaction effect between the use of augmented reality learning media and learning styles on the ability to think about science subject matter